Exploring music contents 7th International Symposium, CMMR 2010, Málaga, Spain, June 21-24, 2010. Revised Papers - CMMR (Symposium) 2010 Málaga, Spain); Ystad, Sølvi; Aramaki, Mitsuko; Kronland-Martinet, Richard .; Jensen, Kristoffer; ringerLink (Online service). (Berlin Heidelberg Springer, 2011)
This book constitutes the thoroughly refereed post-proceedings of the 7th International Symposium on Computer Music Modeling and Retrieval, CMMR 2010, held in Málaga, Spain, in June 2010. The 22 revised full papers presented were specially reviewed and revised for inclusion in this proceedings volume. The book is divided in five main chapters which reflect the present challenges within the field of computer music modeling and retrieval. The chapters range from music interaction, composition tools and sound source separation to data mining and music libraries. One chapter is also dedicated to perceptual and cognitive aspects that are currently subject to increased interest in the MIR community.
Electronic reproduction.
Keywords: Computer music -- Congresses; Information retrieval -- Congresses; Data mining -- Congresses; Musical analysis -- Data processing -- Congresses..; Electronic books